THE MAIN FEATURES OF THE GEOLOGICAL STRUCTURE AND PERSPECTIVES OF KHDEBANTS GOLD ORE MANIFESTATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2002)
The article discusses the geological structure of Khdebants gold ore manifestation which is localized in the skams. The comparative characteristic of that ore manifestation with well studied deposits of that type is given. Based on the analysis of existing geological information conclusions are made on both Khdebants ore manifestation and "scam" gold of Zangezur.
Keywords: Khdebants gold ore manifestation; "scam" gold of Zangezur; skams